Examining the Impact of Obesity on Individuals with Chronic Fatigue Syndrome. (July 2013) - Flores, Samantha; Brown, Abigail; Adeoye, Samuel; Jason, Leonard A.; Evans, Meredyth
Chronic fatigue syndrome (CFS) is a complex disorder affecting multiple body systems. The most commonly used definition of CFS is 6 or more months of fatigue and the presence of at least four of eight minor symptoms. In addition, many health and psychological conditions, including severe obesity–body mass index (BMI) of 40 kg/m 2 or greater–exclude individuals from a diagnosis of CFS. Obesity has been correlated with fatigue, sleep problems, and less satisfaction with general health, functioning, and vitality. The current study investigated weight trends over time in a community-based sample of individuals with CFS and healthy controls. The study further investigated the impact of comorbid weight issues on several health and disability outcomes in a subset of overweight individuals. Overweight and obese individuals with CFS demonstrated poorer functioning than controls who were similarly weighted One participant was excluded because she had gained weight at a monitoring visit and her BMI was greater than 40 kg/m 2 . The implications of these findings for health care workers are discussed.